The solemn sentence of death: capital punishment in Connecticut - Goodheart, Lawrence B. (University of Massachusetts Press, 2011)
Introduction: the paradox of capital punishment -- Biblical retribution, 1636/1699 -- The emergence of Yankee justice, 1700/1772 -- The era of Newgate Prison, 1773/1827 -- The debate over capital punishment, 1828/1879 -- The menace of the criminal class, 1880/1929 -- The waning of executions, 1930/1960 -- An unofficial moratorium, 1961/2004 -- The execution of Michael Ross, 2005 -- Epilogue: an unworkable death penalty